Description and Comparative Genomics of Algirhabdus cladophorae gen. nov., sp. nov., a Novel Aerobic Anoxygenic Phototrophic Bacterial Epibiont Associated with the Green Alga Cladophora stimpsonii - Olga Nedashkovskaya; Sergey Baldaev; Alexander Ivaschenko; Evgenia Bystritskaya; Natalia Zhukova; Viacheslav Eremeev; Andrey Kukhlevskiy; Valeria Kurilenko; Marina Isaeva (Life)
A novel, strictly aerobic, non-motile, and pink-pigmented bacterium, designated 7Alg 153T, was isolated from the Pacific green alga Cladophora stimpsonii. Strain 7Alg 153T was able to grow at 4–32 °C in the presence of 1.5–4% NaCl and hydrolyze L-tyrosine, gelatin, aesculin, Tweens 20, 40, and 80 and urea, as well as produce catalase, oxidase, and nitrate reductase. The novel strain 7Alg 153T showed the highest similarity of 96.75% with Pseudaestuariivita rosea H15T, followed by Thalassobius litorarius MME-075T (96.60%), Thalassobius mangrovi GS-10T (96.53%), Tritonibacter litoralis SM1979T (96.45%), and Marivita cryptomonadis CL-SK44T (96.38%), indicating that it belongs to the family Roseobacteraceae, the order Rhodobacteales, the class Alphaproteobacteria, and the phylum Pseudomonadota. The respiratory ubiquinone was Q-10. The main polar lipids were phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol, phosphatidylcholine, two unidentified aminolipids, and one unidentified lipid. The predominant cellular fatty acids (>5%) were C18:1 ω7c, C16:0, C18:0, and 11-methyl C18:1 ω7c. The 7Alg 153T genome is composed of a single circular chromosome of 3,786,800 bp and two circular plasmids of 53,157 bp and 37,459 bp, respectively. Pan-genome analysis showed that the 7Alg 153T genome contains 33 genus-specific clusters spanning 92 genes. The COG20-annotated singletons were more often related to signal transduction mechanisms, cell membrane biogenesis, transcription, and transport, and the metabolism of amino acids. The complete photosynthetic gene cluster (PGC) for aerobic anoxygenic photosynthesis (AAP) was found on a 53 kb plasmid. Based on the phylogenetic evidence and phenotypic and chemotaxonomic characteristics, the novel isolate represents a novel genus and species within the family Roseobacteraceae, for which the name Algirhabdus cladophorae gen. nov., sp. nov. is proposed. The type strain is 7Alg 153T (=KCTC 72606T = KMM 6494T).